Ergonomics Ship Approach Impact Analysis on the Ability to Provide the Services and Productivity of Pokdarwis in Sangeh Badung Bali - Dewi Irwanti, Ni Ketut; Bayu Wisnawa, I Made; Agustini Karta, Ni Luh Putu (Akademi Komunitas MAPINDO, 2023)
This research was conducted to analyze the effect of the ergonomics approach through SHIP on the ability to provide services and productivity of the Sangeh Village Pokdarwis and to analyze the effect of the ability to provide services on the productivity of the Sangeh Village Pokdarwis. The number of Pokdarwis used as samples n this study were 43 respondents. Data collection was carried out by distributing questionnaires containing 10 statement tems representing 10 ndicators of the three variables used. Data analysis used Smart PLS version 3. The results showed that SHIP (X1) had a positive and significant effect on the Ability to Provide Service (X2) with a value of 11.189, and a p-value of 0.000. SHIP (X2) has a positive and significant effect on productivity (Y) with a value of 3.828 and a p-value of 0.000. The ability to provide services (X2) has a positive and significant effect on productivity (Y) on Pokdarwis (Tourism Awareness Group) n Sangeh Badung Village with a value of 9.432 with a p-value of 0.000. Based on these findings, t s suggested to ntegrate Ergonomics through the SHIP approach n the development of the Sangeh Badung Bali tourism village. Keywords: Ergonomics, SHIP Approach, Serviceability, Productivity